Bilateral Sagittal Split Mandibular Ramus Osteotomy Alters the Temporomandibular Joint. Issue 6 (September 2021) - Wang, Xiangshen; Sun, Xiumei; Wu, Guomin
Abstract : Abstract: In this retrospective analysis, we examined temporomandibular joint space volume and condyle position in 10 patients undergoing bilateral sagittal split mandibular ramus osteotomy plus Le Fort I osteotomy to correct mandibular asymmetry. Cone beam computed tomography was used to map temporomandibular joint prior to (T0), immediately after (T1), and at 1 year after surgery (T2). In the deviated side, we detected significant lateral shift of the condyle in 5 patients at T1, and the shift disappeared at T2. In the non-deviated side, we detected significant medial shift of the condyle in all 10 patients at T1; the shift continued in 9 patients at T2. Temporomandibular joint space volume increased significantly at T1 and returned to presurgical volume at T2. In conclusion, there is significant shift in position of condyle in majority of the patients after bilateral sagittal split mandibular ramus osteotomy. The most consistent and persisting change was medial shift on the nondeviated side. Abstract : Supplemental Digital Content is available in the text